Exploring Students’ Perceptions of the Padlet Application as a Media to Learn Narrative Text - Hertiki, Hertiki; Fransiska, Ajeng Aprilia (Journal of English for Academic and Specific Purposes (JEASP), 2023)
The narrative text is an interesting type of text because it contains a lot of knowledge for writers or readers. Narrative text types are divided into 4. They are fairy tales; folk tales; fables; and legends. Most students like stories that are accompanied by pictures and narrative texts used. This research aims to introduce students to technology-based media as narrative text media. The learning process application supports narrative text to make it more accessible and more attractive to students by using the Padlet Application. The researcher used a qualitative method, and the data source was students in grade 11 IPA 1 at SMAN 1 Wringinanom. Data collection techniques using interviews, observation, and documents. Data analysis techniques using thematic analysis. This research indicates that students prefer to write narrative texts using the Padlet Application rather than the conventional method. The Padlet Application can make time more efficient, easy, interesting, and fun. This is demonstrated through interviews, observations, and documents conducted by the researcher.